The Effect of Supervision Implemented by Principals on Guidance and Counseling Services at State Junior High Schools in Malang City - Safitri, Berlian Ayu; Sunandar, Asep; Sumarsono, Raden Bambang (Proceedings Series of Educational Studies, 2024)
Educational institutions certainly want to improve the quality of school services in order to educational goals optimally. Guidance and counseling services aim to help students achieve academic goals, be able to decide, and responsible themselves and their environment. The quality control is then needed to entire process and supporting components. Principal as a supervisor must be able to coordinate the supervisor program all components. This study aims to describe how the effect of the implementation of supervision carried out on guidance and counseling services. This research was conducted at public junior high schools in Malang City. The method used is quantitative approach with descriptive research design, data processing using SPSS application. The results of the study obtained: (1) principals have implemented supervision techniques both individually and in groups well; (2) guidance and counseling services provided to students in public junior high schools in Malang City have been implemented according to the components of counseling guidance services well; (3) there is a positive influence of supervision on guidance and counseling services at public junior high schools in Malang City. Keywords: effect; supervision; supervision techniques; guidance and counseling services